2003
DOI: 10.1081/ceh-120020391
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methylenetetrahydrofolate Reductase C677T Common Variant on Hypertensive Risk Is Not Solely Explained by Increased Plasma Homocysteine Values

Abstract: The C677T transition of methylenetetrahydrofolate reductase (MTHFR) gene causes a moderate increase in total plasma homocysteine (tHcy). We studied the effect of MTHFR TT homozygosity and mild hyperhomocysteinemia on arterial hypertension. Normotensive controls (n = 223) and hypertensive subjects (n = 235) were matched for age, gender, and history of cardiovascular disease. Homocysteine levels were measured by a polarization immunoassay method. Methylenetetrahydrofolate reductase we determined by polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
4
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
3
17
4
1
Order By: Relevance
“…Some studies have reported a gender specific association; one large population study in >3000 Japanese individuals reported that the MTHFR 677C T polymorphism was associated with a 42 % increased risk of hypertension in women but not in men (96) . In contrast, in a Spanish cohort, the TT genotype was found to be a significant predictor of hypertension in men but not in women, however, only 26 % of the sample were females (100) .…”
Section: Novel Role Of Mthfr Genotype and Blood Pressurecontrasting
confidence: 59%
“…Some studies have reported a gender specific association; one large population study in >3000 Japanese individuals reported that the MTHFR 677C T polymorphism was associated with a 42 % increased risk of hypertension in women but not in men (96) . In contrast, in a Spanish cohort, the TT genotype was found to be a significant predictor of hypertension in men but not in women, however, only 26 % of the sample were females (100) .…”
Section: Novel Role Of Mthfr Genotype and Blood Pressurecontrasting
confidence: 59%
“…Our results did not reveal any gender-related differences with respect to the MTHFR C677T polymorphism and hypertension. These results are contrary to those obtained in Spain where the MTHFR TT genotype could predict the development of EH in males (Rodríguez-Esparragón et al, 2003). Our results confirm the fact that differences in ethnicity and geographical location could genetically predispose individuals to hypertension (Hong et al, 2010;Xi et al, 2014).…”
Section: Discussioncontrasting
confidence: 57%
“…Additionally, the significant association between C677T polymorphism and hypertension/ hypertension-in-pregnancy suggests that this polymorphism is an independent risk factor of hypertension (Qian et al, 2007). Consistently, studies in Asian populations (Markan et al, 2007) and Spanish subjects (Rodríguez-Esparragón et al, 2003) on the C677T polymorphism in the MTHFR gene revealed similar results. However, the involvement of the MTHFR C677T polymorphism is not consistent in all populations.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Several other studies have failed to observe any significant relationship between the MTHFR polymorphism or homocysteine and BP (83,84) . Evidence of an independent relationship between the MTHFR polymorphism and BP has been noted (85) . While mean homocysteine concentrations were found to be significantly higher in men with hypertension, with homocysteine concentrations ‡15 mmol/l being associated with increased risk of hypertension, interestingly this outcome was not observed in men without the TT genotype but with similar homocysteine concentrations.…”
Section: Homocysteine Lowering (Via B-vitamin Supplementation) and Blmentioning
confidence: 99%